Monoclonal Antibodies as Probes to Study Ligand-Induced Conformations of Troponin Subunits - Rasmussen, Monica; Jin, Jian-Ping (Frontiers in Physiology, 2022)
Striated muscle contraction and relaxation is regulated by Ca2+ at the myofilament level via conformational modulations of the troponin complex. To understand the structure–function relationship of troponin in normal muscle and in myopathies, it is necessary to study the functional effects of troponin isoforms and mutations at the level of allosteric conformations of troponin subunits. Traditional methodologies assessing such conformational studies are laborious and require significant amounts of purified protein, while many current methodologies require non-physiological conditions or labeling of the protein, which may affect their physiological conformation and function. To address these issues, we developed a novel approach using site-specific monoclonal antibodies (mAb) as molecular probes to detect and monitor conformational changes of proteins. Here, we present examples for its application in studies of two subunits of troponin: the Ca2+-binding subunit, TnC, and the tropomyosin-binding/thin filament-anchoring subunit, TnT. Studies using a high-throughput microplate assay are compared with that using localized surface plasmon resonance (LSPR) to demonstrate the effectiveness of using mAb probes to assess ligand-induced conformations of troponin subunits in physiological conditions. The assays utilize relatively small amounts of protein and are free of protein modification, which may bias results. Detailed methodologies using various monoclonal antibodies (mAbs) are discussed with considerations for the optimization of assay conditions and the broader application in studies of other proteins as well as in screening of therapeutic reagents that bind a specific target site with conformational and functional effects.